Use of Natural and Cultural Resources by Tourism as a Strategy for Regional Development: Bibliometric Analysis - Claudia Patricia Maldonado-Erazo; María de la Cruz del Río-Rama; José Álvarez-García; Ana Carola Flores-Mancheno (Land, 2022)
Territories throughout different continents have a wide variety of natural and cultural resources, defined by the dynamics of spatiality, temporality, and functionality that have been generated by the human groups settled in these spaces. These resources have become an object of study of great interest since they constitute the initial sources for the definition of the tourism potential of destinations, as well as contributing to the generation of new tourism activities and modalities for those already consolidated. Although these resources were initially used as objects of exploitation, with the passage of time the dynamics have changed to the use of these resources, focusing on the foundation of the pillars of sustainability, a condition that implies practices of environmental valuation in situ, the recognition of the cultural heritage of the territories and the valuation of the interaction between culture–nature–human beings. The objective of this research is to identify the existing scientific production in which the relationship between the tourist exploitation of natural and cultural resources and regional development is explored. Bibliometric analysis based on the guidelines of the PRISMA method was used. The international databases considered were Web of Science and Scopus. The analysis was complemented with an overlap analysis to establish the relationship of information between the WoS and Scopus databases. A total of 507 documents on the subject were identified, which provided a preliminary X-ray that will allow future research work to be focused on this line of re-search. The results allowed us to observe that there is little literature on the relationship between the use of natural and cultural resources for tourism and the regional development of the territory, both from an economic and social point of view.